Autoethnography: introducing 'I' into medical education research. Issue 10 (18th September 2015) - Farrell, Laura; Bourgeois‐Law, Gisele; Regehr, Glenn; Ajjawi, Rola
<x xml:space="preserve">Abstract</x> Discuss ideas arising from the article at www.mededuc.com discuss.